Nelson Mandela: The Absent Cause - Gikandi, Simon (Journal of the African Literature Association, 2016)
[...]when a colleague asks me to speak at a local forum commemorating Mandela's life, I can't escape into silence, nor can I just turn up and declare, in the words of Williams Carlos Williams that Of death the barber the barber talked to me cutting my life with sleep to trim my hair- It's just a moment he said, we die every night- ("Spring and All") So I will stay up all night trying to think about the role of the imagination in the life of Nelson Mandela, the icon of freedom in our times, and his influence on the forms of art in South Africa. [...]I will first hear his name in the sorrow songs of South African exiles in East Africa and over the shortwave bands of the African National Congress, broadcasting from Lusaka, Zambia. [...]the question is put to me more specifically: Written from the vantage point of arrival, Long Walk to Freedom sets to confirm the prophetic idea that out of the hills of Qunu a leader will emerge to lead his people out of bondage; tied to this allegory of the world historical individual, the autobiography fails to account for the vulnerability of the subject, or to acknowledge the challenges of incomplete histories.